Near IR sensitization of organic bulk heterojunction solar cells: Towards optimization of the spectral response of organic solar cells - Koppe, Markus; Egelhaaf, Hans-Joachim; Dennler, Gilles; Scharber, Markus C.; Brabec, Christoph; Schilinsky, Pavel; Hoth, Claudia N. (Advanced Functional Materials, 2010)
The spectroscopic response of a poly(3-hexylthiophene)/[6,6]-phenyl-C -butyric acid methyl ester (P3HT/PCBM)-based bulk heterojunction solar cell is extended into the near infrared region (NIR) of the spectrum by adding the low bandgap polymer polyp,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1 -b, 3, 4-b]-dithiophene)-alt-4, 7-(2, l, 3-benzothiadiazole)] [PCPDTBTJ to the blend. The dominant mechanism behind the enhanced photosensitivity of the ternary blend is found to be a two-step process: first, an ultrafast and efficient photoinduced charge transfer generates positive charges on P3HT and PCPDTBT and a negative charge on PCBM. In a second step, the positive charge on PCPDTBT is transferred to P3HT. Thus, P3HT serves two purposes. On the one hand it is involved in the generation of charge carriers by the photoinduced electron transfer to PCBM, and, on the other hand, it forms the charge transport matrix for the positive carriers transferred from PCPDTBT. Other mechanisms, such as energy transfer or photoinduced charge transfer directly between the two polymers, are found to be absent or negligible. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA.